Capacity Building in Response of Tidal Floods in Belawan II, North Sumatra - Utami, Rahmi; Khair, Hafizhul; Lubis, Arliza Juairiani (Talenta Publisher, 2023)
Belawan II is located in Medan Belawan District – North Sumatra, which often experiences tidal floods. The low ground level, the use of pump wells as a source of clean water, the behavior of throwing garbage into the river and poor drainage conditions make tidal flooding uncontrollable, including in. The potential increase in the threat of tidal flooding in Belawan II has an impact on increasing the vulnerability of people's lives and livelihoods. But on the other hand, local leaders and communities accept tidal flooding as a natural phenomenon in coastal areas, so they do not consider this threat a disaster. Belawan II has never planned a disaster risk study to seek mitigation that is oriented towards increasing awareness and ability to deal with, reduce, and overcome the impact of tidal flooding. Reducing the risk of tidal flood threat problems in Belawan II is carried out with a community-based approach. The development of the resilient city program in Belawan II is a solution by facilitating increased knowledge, awareness, and ability of local communities. The activities include assessing, analyzing, handling, monitoring, evaluating, and reducing disaster risks in the Belawan II area.